A demonstration apparatus for gas solid chromatography - Espejo, Milagros A. 1944- (1965)
An inexpensive apparatus for lecture demonstration was constructed to effect satisfactory seperation of mixtures of several organic liquids by gas solid chromatography. Components of mixtures are detected by visual observation of changes in the nature of the height of a hydrogen flame. An inductive method of presenting the principle involved in gas solid chromatography to a high school class was described.